2018
DOI: 10.1519/jsc.0000000000001787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Training to Muscle Failure vs. Volitional Interruption at High- and Low-Intensities on Muscle Mass and Strength

Abstract: Nóbrega, SR, Ugrinowitsch, C, Pintanel, L, Barcelos, C, and Libardi, CA. Effect of resistance training to muscle failure vs. volitional interruption at high- and low-intensities on muscle mass and strength. J Strength Cond Res 32(1): 162-169, 2018-The purpose of this study was to investigate the effects of resistance training (RT) at high- and low-intensities performed to muscle failure or volitional interruption on muscle strength, cross-sectional area (CSA), pennation angle (PA), and muscle activation. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
119
2
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(163 citation statements)
references
References 38 publications
12
119
2
22
Order By: Relevance
“…Therefore, future studies with a larger number of individuals may be necessary to confirm the present findings. Despite this limitation, in agreement with our results, Nóbrega et al submitted young men to knee extension ST for 12 weeks, and they observed similar improvements in maximal strength and muscular hypertrophy among groups performing repetitions to failure and not to failure, independent of ST intensity and even without volume compensation. Taken together, these findings indicate that performing repetitions leading to concentric failure is not critical for inducing increases in strength and muscle size when sufficient ST intensity is achieved.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, future studies with a larger number of individuals may be necessary to confirm the present findings. Despite this limitation, in agreement with our results, Nóbrega et al submitted young men to knee extension ST for 12 weeks, and they observed similar improvements in maximal strength and muscular hypertrophy among groups performing repetitions to failure and not to failure, independent of ST intensity and even without volume compensation. Taken together, these findings indicate that performing repetitions leading to concentric failure is not critical for inducing increases in strength and muscle size when sufficient ST intensity is achieved.…”
Section: Discussionsupporting
confidence: 92%
“…After the intervention period, the improvements found in the lower limb maximal dynamic and isometric strength (PT iso ) were in agreement with gains observed in previous studies investigating CT in older men . Regarding the use of repetitions to failure or not to failure, our findings are in accordance with those of other studies that carried out similar comparisons over shorter training periods (from 6 to 16 weeks) in young and older individuals . In a previous study performed in our laboratory, Da Silva et al showed that 12 weeks of CT induced marked adaptations in the maximal dynamic strength and isometric peak torque of the lower limbs, regardless of whether repetitions to failure or greater ST volumes were used.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations